Multibeam bathymetry raw data (Kongsberg EM 122 entire dataset) of RV MARIA S. MERIAN during cruise MSM110 - Helmuth Thomas; Marit-Solveig Seidenkrantz; Adrián López-Quirós; Joanna Davies; Phoebe Armitage; Mia Schumacher (PANGAEA, 2024)
Raw multibeam bathymetry data were collected aboard RV MARIA S. MERIAN during cruise MSM110 using a Kongsberg EM 122 multibeam echosounder. The expedition took place during 07.08.2022 – 29.08.2022 from Reykjavik to Reykjavik (Iceland) in the Northern Atlantic Ocean. Data were recorded in the EEZs of Greenland and Iceland and outside. MSM110 focused on improving our understanding of anthropogenic changes in the biological production and diversity in the Arctic marine regions, and their effects on the ecosystem services as part of the Horizon 2020 project ECOTIP. Sound velocity profiles (SVP) were applied on the data for calibration. Please see environmental data and the cruise report for details. The data are unprocessed and can therefore contain incorrect depth measurements (artifacts) if not further processed. Note that refraction errors may occur when no proper SVP is applied. Acquisition and provision of the data are part of the DAM Underway Project and are according to the FAIR principles.